Kajian Teologis Respon Masyarakat Muslim Terhadap Covid-19 dan Dampak Perilaku Beragama - Siti Latifah; Uswatun Hasanah (Prodi Tasawuf dan Psikoterapi, Fakultas Agama Islam, Universitas Muhammadiyah Cirebon, 2021)
This research discusses the theological perception of the Muslim community, especially the perspective of the Jabariyyah and Qadariyyah schools, in responding to the Covid-19 pandemic. As we all know, the development of Covid 19 that occurred in March 2020 had a major impact throughout the world. And Indonesia is one of the affected countries. As a country where the majority of the population is Muslim, the Muslim community has its own response in dealing with the Covid-19 virus; some groups consider this virus as a destiny that has been outlined by Allah SWT, while others think that this virus is spreading because of pure human negligence, whether intentional or not. In this regard, as a form of concern for the impact caused by Covid 19, several movements have emerged that aim to help survivors of Covid 19. This is done so that all parties can fight together through this pandemic period and learn from the handling of the outbreak since the time of the Prophet Muhammad. This research uses the method of searching Islamic literature, starting from analyzing and describing it.